The Lived Experiences of Beginning Teachers: An Odyssey - Marissa Mendoza (Philippine Association of Institutions for Research, Inc., 2020)
The attrition rates for beginning teachers have been high and widespread, which oftentimes resulted in a teacher shortage. This qualitative phenomenological study explored the lived experiences of beginning teachers during their first three years in teaching. Specifically, it digs a deeper understanding of the challenges beginning teachers face, such as classroom management, support received, differentiated instruction, and unexpected expectations. An in-depth interview was conducted to ten beginning junior high school teachers from public and private schools within DepEd Puerto Princesa. Member checking was done to validate the accuracy of the data and to establish credibility.  The four constructs of credibility, transferability, dependability, and confirmability were considered to substantiate trustworthiness. The study reveals that beginning teachers are mostly challenged by the behavior of the students in classroom management; get the needed support from their administrators, colleagues, students' parents, and immediate families; find difficulty in differentiating instruction to address learner's differences; and are overwhelmed by the enormous amount of paperwork, extra-curricular assignments and teaching subjects not in line with their specialization. Likewise, salary, lack of training and orientation, work environment, and workload emerged as minor themes. Thus, beginning teachers' found their first three years as challenging, overwhelming, shocking, tiring, difficult, stressful, and struggle yet wonderful, exciting, fun, colorful, rewarding, and fulfilling.